Teaching Geoheritage Values: Implementation and Thematic Analysis Evaluation of a Synchronous Online Educational Approach - Georgousis, Efthymios; Savelidi, Maria; Savelides, Socrates; Holokolos, Maximos-Vasileios; Hara Drinia (Heritage, 2021)
The purpose of this article is to present the results of an environmental education program on “Storm-Tossed Sea Rocks in Pelion Seaside” designed for junior high school students and implemented as a synchronous online educational approach and with a main goal to empower students to the values of geoheritage. In order to examine the effectiveness of the program and in particular the achievement of the objectives that encourage the development of values, the research question was identified as to whether the implementation of the environmental program achieved the empowerment of students in geoheritage values. In order to answer this question, we implemented a rather unusual technique to evaluate the educational procedure, which was based on the qualitative research technique of thematic analysis. This technique was selected as the most appropriate in order to “mine” conceptual patterns, the analysis of which would, in a valid, reliable, and simultaneously easy to use and quick way, inform the teachers that the values of geoheritage were disseminated to the students through the program. Thus, four-question interviews were conducted with randomly selected students who participated in the program. The data were examined and conceptual patterns were identified which were classified in eighteen codes. The codes were divided into five categories, the analysis of which led to the answer to the research question. Thus, it was found that the implementation of the environmental program achieved the empowerment of students in geocultural heritage values. The development of feelings of environmental sensitivity has also been seen, which suggests further investigation is needed. It was concluded that for the students, the given educational approach was necessary as well as cognitively, pedagogically, and emotionally beneficial; therefore, the need to enrich the curricula of environmental education/education for sustainable development with issues of geodiversity and geocultural heritage is justified. Finally, what was ascertained is that the thematic-analysis-based evaluation technique of the educational procedure, which was implemented, provided the teachers with the requested information, and it is recommended as an evaluation technique of educational procedures which aim at empowering students on values—even for daily use in school.